Curricular strategies of public universities that focus on teaching English in early childhood education - Galvao, Ana Sara; Kawachi-Furlan, Cláudia (Calidoscópio, 2023)
This article discusses English teacher education to work in early childhood education. The offer of English for this age group is an increasing reality in Brazilian contexts and, therefore, the demand for specific teacher education for this field is also expanding. Considering this scenario, the research conducted had the aim of analyzing curricular proposals of majors in English and Literature in Brazilian Federal and State Universities, focused on initial education of teachers to work with children. After searching on the E-MEC website, 108 institutions were listed as part of the research. The documentary survey resulted in 15 universities with approaches that met the criteria established by the researchers, which also had significant contributions regarding the initiatives implemented in those universities. Moreover, with the goal of also investigating local realities, five institutions were invited to participate in an interview. Through reflections based on curricular theories, transdisciplinarity, teacher education and teaching English to young learners, the research offered a national overview and local aspects around the topic. Furthermore, the results presented in this article point out to the possibilities of understanding English teacher education to work with children as a new space, closely related to the local context and marked by particularities. Keywords: Teacher education; curriculum; Teaching English to young learners.